Impact of childcare center facilities on working mothers’ performance at office: A study on Bangladesh - Shaulin, Nahida (Brawijaya Journal of Social Science, 2024)
In Bangladesh, it is a prevalent occurrence for working women to experience heightened concerns over the safety and well-being of their children following childbirth The primary aim of the study is to investigate the impact of childcare facilities on the occupational productivity of employed women in Bangladesh. The study has been conducted following a quantitative method research approach. The area of study is Dhaka City. The statistical tests performed in this study include frequency distribution, descriptive statistics, reliability analysis, and chi-square test. By conducting a chi-square test (p<0.05), the overall study revealed that there is a relationship between childcare center facilities and the working mother's performance at the workplace. The findings of the study pointed out that the majority of the participants believe that reliable childcare facilities have a positive impact on maintaining their work-life balance. The findings of this study will provide valuable insights for policymakers to be more concerned about establishing reliable childcare facilities in Dhaka city so that the active participation of working mothers in the workplace increases and they can promote their ability to deliver high-quality performance at their workplace. Over the last decade, a significant amount of scholarly inquiry has been dedicated to the area of women's empowerment and the augmentation of female representation within the labor market. But this study is the first to highlight the impact of childcare center facilities on working mothers performance at office.